Symbols and legitimacy in Soviet politics - Gill, Graeme J. (Cambridge University Press, 2011)
"Symbols and legitimacy in Soviet politics analyses the way in which Soviet symbolism and ritual changed from the regime's birth in 1917 to its fall in 1991. Graeme Gill focuses on the symbolism in party policy and leaders' speeches, artwork and political posters, urban redevelopment, and on ritual in the political system. He shows how this symbolism and ritual were worked into a dominant metanarrative which underpinned Soviet political development. Gill also shows how, in each of these spheres, the images changed both over the life of the regime and during particular stages: the Leninist era metanarrative differed from that of the Stalin period, which differed from that of the Khrushchev and Brezhnev periods, which was, in turn, changed significantly under Gorbachev. In charting this development, the book lays bare the dynamics of the Soviet regime and a major reason for its fall"--Provided by publisher.